Controlled human infections: A report from the controlled human infection models workshop, Leiden University Medical Centre 4–6 May 2016. Issue 51 (18th December 2017) - Roestenberg, Meta; Mo, Annie; Kremsner, Peter G.; Yazdanbakhsh, Maria
Highlights: Controlled human infection (CHI) models are diverse but face similar challenges. CHI are increasingly used to select products for downstream development. A CHI platform for researchers would be instrumental to share best practices. Abstract: The principle of deliberately infecting humans with infectious agents in a controlled setting, so-called controlled human infections (CHI), is not novel. Many CHI models have a long history and were established decades ago such as the intentional exposure to yellow fever and dengue performed in the 1900's (Reed, 1902) [2]. In these times bioethics and scientific reasoning were in their infancy. Nowadays, clinical trials are highly regulated and CHI are executed worldwide. Controlled human malaria infections and influenza infections are the two most frequently practiced. Others are experiencing a revival or are being carefully developed. Because CHI models test the efficacy of promising vaccine or drug candidates early in clinical development, they offer the potential to decrease the number of failing phase 2 and 3 trials, reducing risks for patients and saving costs and efforts. In addition, CHI models provide unprecedented opportunities to dissect the physiological, immunological and metabolic changes that occur upon infection. However, it is clear that controlled infections require careful deliberation of safety, ethics, quarantine, scientific output and the production of infectious material. An independent international workshop was hosted by the Leiden University Medical Centre in The Netherlands, bringing together clinical investigators, basic scientists, regulators, funders and policy makers from 22 different countries to discuss the opportunities and challenges in CHI. The aim of the workshop was to discuss CHI as a tool to advance science, drug and vaccine development, share the challenges of establishing a CHI model with specific focus on neglected tropical diseases and the possibilities to transfer models to endemic sites. Noticeably, among the 128 participants were clinical investigators from ten different countries in Sub-Saharan Africa. An important dimension of the meeting was to give the floor to young established clinicians and scientists to voice their perspective on the future of CHI models.